THE GLOBAL ECONOMIC DEVELOPMENT OF RICE IN UZBEKISTAN - Ozodbekova Azizakhon Pulatjon qizi; Tuychieva Mukhlisa Toxir Tohir qizi (Modern American Journals, 2025)
One of the most conspicuous trends in the 21st century is the global economic development of rice. There is widespread worry that this will lead to the gradual depletion of rice in the countries. Some of the reasons are rice pest control, multi-functionality of the rice production system, local rice price, trade and marketing policies, etc. These are common problems in almost all countries but can be a minor problem in today's era of globalization. will have negative consequences in the future, so it is important to know about the scarcity of rice and how important it is. There is no shortage of rice in Uzbekistan, but this does not mean that it will not happen in the future. That is why the government is taking several measures.